Aportaciones sobre la interpretación, ecología y distribución de los bosques supratemplados naviano-ancarenses - Rodríguez-Guitián, Manuel A.; Amigo Vázquez, Javier; Romero Franco, Rosa (Lazaroa, 2000)
Rodríguez Guitián, M.A., Amigo Vázquez, J. & Romero Franco, R. On the classification, ecology and distribution of the supratemperate woodlands of the Navian-Ancarian subsector in the north-west of the Iberian Peninsula. Lazaroa 21: 51-71 (2001). On the basis of previous reports and our own field data, we reassess the woodland types present in the Navian-Ancarian Subsector (Lacian-Ancarian Sector, Oro-Cantabrian Subprovince) in the north-west of the Iberian Peninsula. Considering the ranks of subassociation, variant and facies, we identified a total of 15 climatophilous types, 4 edaphohygrophilous types, 4 succession-community types, and 2 pioneer coloniser types. These conclusions form the basis for defining the vegetation series present in this subsector, and for discussion of geobotanical similarities and differences with respect to the Lacian-Narceen Subsector. corológica (RIVAS-MARTÍNEZ & al., 1991, GIMÉNEZ